Antiarthritic effect of aqueous and ethanolic leaf extracts of Pistia stratiotes in adjuvant-induced arthritis in Sprague-Dawley rats - Kyei S; Koffuor GA; Boampong JN (Dove Medical Press, 2012)
Samuel Kyei1, George A Koffuor1, Johnson N Boampong21Department of Pharmacology, Faculty of Pharmacy and Pharmaceutical Sciences, College of Health Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana; 2Department of Human Biology, School of Biological Sciences, University of Cape Coast, Cape Coast, GhanaBackground: Pistia stratiotes has been used effectively to treat a number of inflammatory conditions. This study aims to determine the antiarthritic effect of aqueous and ethanolic leaf extracts of P. stratiotes.Methods: Arthritis was induced in Sprague-Dawley rats, paw swelling was measured, and arthritis indices were estimated in rats treated with aqueous and ethanolic leaf extracts of P. stratiotes (AQ PSE and ET PSE, respectively), methotrexate, diclofenac, dexamethasone, and normal saline-treated rats. Radiologic imaging, hematological assessment of red and white blood cells, C-reactive protein and erythrocyte sedimentation rate, as well as histopathological studies were also done. The data were analyzed using GraphPad Prism 5.Results: The 30, 100, and 300 mg/kg doses of AQ PSE and the 30 and 100 mg/kg doses of ET PSE caused a significant (P ≤ 0.05–0.001) reduction in ipsilateral paw swelling, similar to the effects of methotrexate, dexamethasone, and diclofenac. Only the 30 mg/kg dose of AQ PSE caused a significant (P ≤ 0.01) reduction in contralateral paw swelling. Arthritic indices reduced significantly (P ≤ 0.05–0.001) at all drug doses, except for the 100 and 300 mg/kg doses of ET PSE. White blood cell levels decreased significantly (P ≤ 0.05–0.01) in arthritic rats treated with the 30 mg/kg dose of AQ PSE and those treated with methotrexate. Erythrocyte sedimentation rate and C-reactive protein levels were significantly (P ≤ 0.01–0.001) lower in all the treatment groups except for the rats treated with AQ PSE 300 mg/kg and ET PSE 100 and 300 mg/kg doses. The arthritic animals treated with 30 mg/kg of the aqueous extract showed no inflammatory changes in the ipsilateral paw, while the contralateral paw showed only foci of mild chronic inflammatory changes, as seen with the reference drug treatment in histopathological studies.Conclusion: This study establishes that aqueous and ethanolic extracts of P. stratiotes have antiarthritic activity in Sprague-Dawley rats with induced arthritis. The aqueous extract had better activity than the ethanolic extract.Keywords: Pistia stratiotes, arthritic index, radiological index, C-reactive protein, ipsilateral paw, inflammation